2022
DOI: 10.20885/jeki.vol8.iss1.art4
|View full text |Cite
|
Sign up to set email alerts
|

Islamic Finance and Indonesia's Economy: An Empirical Analysis

Abstract: Purpose – Islamic finance is becoming increasingly important both globally and in Indonesia. However, studies on the relationship between Islamic finance and Indonesia’s economy are scant. Therefore, this study aims to analyse the short-term and long-term relationship between Islamic finance and Indonesia’s economy.   Methodology – This study uses monthly data for the period 2011–2020 which are estimated using the Vector Error Correction Model (VECM). The dependent variable is Indonesia’s Growth Domestic Produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…The results presented in Table 6 demonstrated that Ln(IBA) has a coefficient value (0.224) and p-value of 0.003**; it positively and significantly impacted the Ln(GDP) in the long run. Thus, the result for (H1) is analogous with the findings of Khaliq and Thaker (2017), Jawad and Christian (2019) and Sakinah et al (2022) where Islamic banking assets and real GDP can exhibit a positive long-run relationship, indicating an improvement in the quality of assets. Hence, the proposition (H1) for model Ln(IBA) is fully supported.…”
Section: Autoregressive Distributed Lag Model: Estimation Of Long-run...supporting
confidence: 79%
See 2 more Smart Citations
“…The results presented in Table 6 demonstrated that Ln(IBA) has a coefficient value (0.224) and p-value of 0.003**; it positively and significantly impacted the Ln(GDP) in the long run. Thus, the result for (H1) is analogous with the findings of Khaliq and Thaker (2017), Jawad and Christian (2019) and Sakinah et al (2022) where Islamic banking assets and real GDP can exhibit a positive long-run relationship, indicating an improvement in the quality of assets. Hence, the proposition (H1) for model Ln(IBA) is fully supported.…”
Section: Autoregressive Distributed Lag Model: Estimation Of Long-run...supporting
confidence: 79%
“…Studies discussing the causal relationship of Sukuk and economic growth identified that Sukuk market development can play a key role in long-term economic growth. Smaoui and Nechi (2017), Jallow and Joof (2020), Orhan and Tirman (2021), Ledhem (2022) and Sakinah et al (2022) strongly support supply-leading hypothesis. Few recent studies also investigated reciprocal relation; Basyariah et al (2021) examined how the stability of institutions and macroeconomic factors influence the growth and progress of the global Sukuk market.…”
Section: Islamic Bond and Economic Growthmentioning
confidence: 67%
See 1 more Smart Citation
“…Overall, the Indonesian Islamic finance industry has a market share of 9.95%. 35 Distribution of sharia banking financing in 2020 grew by 8.08%, slower than the previous year, which grew by 10.89%. This slowdown was caused partly by Working Capital financing, which slowed to 4.14% compared to the previous year, which was 6.00%, and investment financing slowed to 0.16% from 14.84% the previous year.…”
Section: Results and Discussion Sharia Leasing In Indonesiamentioning
confidence: 96%
“…Islamic capital market in Indonesia's total assets also grew very aggressively to 1.075,22 trillion rupiahs by the end of December 2020. Islamic banking has total assets of 608,90 trillion rupiahs, and the Islamic nonbank financial sector has 116.22 trillion rupiahs [7]. Islamic finance in Indonesia greatly contributes to economic growth in Indonesia, especially the growth of Islamic banking in Indonesia [8].…”
Section: Literature Reviewmentioning
confidence: 99%